Perancangan Pengalaman Pengguna Aplikasi Pelayanan Publik Online di Kelurahan menggunakan Metode Human-Centered Design (Studi Kasus: Kelurahan Sisir, Kota Batu) - Pungky Aryati; Riswan Septriayadi Sianturi; Ratih Kartika Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Services in Sisir Village, Batu City are performed offline by bringing the RT/RW cover letters and supporting document such as copies of ID cards and family card. Many of queues at the service office, making some requests have to be postponed, while residents didn't have free time to come back because of their business. This study aims to produce a user experience design that is under user expectations in terms of user experience and usability. Human-Centered Design was chosen as the method used in this study. This method prioritizes the user which is carried out in several stages; literature study, usage context analysis, the user needs analysis, solution design, and solution design evaluation. The test was carried out using usability testing which is carried out on 10 respondents. Usability aspects tested include effectiveness, efficiency, and user satisfaction. The results of the effectiveness test obtained a value of 86,43%, the efficiency test obtained a value of 0.1725 goals/second, and the user satisfaction test obtained a score of 68 which was categorized as good and grade scale D, which means the design is still acceptable.